Managing people in a multicultural environment - Moryc, Katarzyna Małgorzata (2016)
The main objective of the thesis was to define and analyze key aspects of managerial work in multicultural environment, in one of the Shared Services Center department, of multinational company based in Prague, Czech Republic. Further thesis aimed to define essential competencies of the successful manager and leader driving performance of multicultural department and provides recommendations to improve managerial performance in key aspects of manager s work such as communication, motivation, performance management and cross-cultural leadership. It is argued that presence of intercultural interactions between managers and their subordinates, impacts effectiveness of the managerial performance. Thesis consists of theoretical and practical part. First part of the thesis explores theoretical concepts regarding culture, communication, motivation and leadership with respect to multicultural environment specifics. In the second part, used research methods, conducted research analysis and outcomes are presented. Further in practical part recommendation towards analyzed aspects of managerial work that would lead to higher overall department performance are defined.